Community Outreach and Engagement to Prepare for Household Recruitment of National Children's Study Participants in a Rural Setting. Issue 1 (1st August 2012) - Fahrenwald, Nancy L.; Wey, Betty; Martin, Ann; Specker, Bonny L.
Abstract Context: The National Children's Study (NCS) is a longitudinal study of environmental influences on children's health. Recruitment of a representative birth cohort that will be followed until 21 years of age requires unique approaches across the nationwide study communities. Purpose: To describe community outreach and engagement in preparation for household recruitment of women of childbearing age at a rural‐classified NCS location that includes 4 adjacent Northern Plains counties spanning 2, 500 square miles. Methods: Outreach and engagement methods focused on rural community characteristics. The team established an advisory council, conducted outreach meetings with agencies and groups, participated in local events, and collaborated with stakeholders. Study awareness was raised using radio announcements, local television stories, and widespread distribution of print materials through churches, businesses, and child care centers. Impact evaluation examined the number of stakeholder events by type. Outcome evaluation examined the number of households contacted for recruitment, numbers of age‐eligible women who completed the screening, and exploration of whether women had heard about the study. Findings: Over 300 outreach events occurred, ranging from tribal council meetings to parade entries. Recruitment outcomes were as follows: (1) 80% of 14, 700 non‐vacant households were reached for potential recruitment; (2) screening interviews were conducted with 89% of the 5, 800 age‐eligible women identified; and (3) 53% of women who completed the screening had heard about the study. Conclusions: Outreach targeted to rural communities facilitated strong recruitment outcomes. Collaboration with the cooperative extension service was a unique rural asset that facilitated relevant activities. Participant retention is an ongoing priority.